CULTURING TAT TWAM ASI VALUES IN EARLY CHILDREN TO MINIMIZE BULLYING - Ni Made Sumaryani (JARITA : Journal of Children’s Education and Learning Research, 2023)
Cases of bullying in the world of education in Indonesia are increasingly concerning. This is shown by the results of a 2014 study by the National Consortium for Character School Development which stated that bullying cases occur in almost every school in Indonesia. This case has a negative impact on various aspects of the lives of children who receive bullying and must be minimized as early as possible. Some literature mentions bullying in several parts, namely verbal, nonverbal and psychological bullying. One method that is effective in minimizing the occurrence of bullying is instilling Tat Twam Asi values ​​from an early age. This article uses a qualitative method with a literature study approach related to instilling Tat Twam Asi values ​​in early childhood in order to minimize bullying. Tat Twam Asi as the basis for Hindu ethics is a guide for moral improvement. Tat Twam Asi teaches equality between human beings, so bullying or bullying is not allowed. On the contrary, Tat Twam Asi emphasizes the love between human beings, this can be seen from its definition that Tat Twam Asi means it is you. One should love one another as one loves oneself.